1994
DOI: 10.1063/1.466914
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectroscopy of NO+(H2O)n: Evidence for the intracluster reaction NO+(H2O)n→H3O+(H2O)n−2 (HONO) at n 4

Abstract: Infrared spectra of mass-selected clusters NOf(H20), for n = 1 to 5 were recorded from 2700 to 3800 cm-' by vibrational predissociation spectroscopy. Vibrational frequencies and intensities were also calculated for n= 1 and 2 at the second-order MQller-Plesset (MP2) level, to aid in the interpretation of the spectra, and at the singles and doubles coupled cluster (CCSD) level energies of it = 1 isomers were computed at the MP2 geometries. The smaller clusters (n = 1 to 3) were complexes of HZ0 ligands bound to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 27 publications
6
58
0
Order By: Relevance
“…The computed IR spectrum for this isomer is in good agreement with experiment in the high-frequency region. The experimental spectrum also shows an additional intense band at approximately 2800 cm −1 , which is interpreted as evidence for the formation of HONO [15]. The lowest energy isomer with HONO identified in the search has a relative energy of +6.3 kJ mol −1 with ZPE included.…”
Section: Density Functional Theory and Mp2 Studies Of No + H 2 O Andmentioning
confidence: 81%
See 1 more Smart Citation
“…The computed IR spectrum for this isomer is in good agreement with experiment in the high-frequency region. The experimental spectrum also shows an additional intense band at approximately 2800 cm −1 , which is interpreted as evidence for the formation of HONO [15]. The lowest energy isomer with HONO identified in the search has a relative energy of +6.3 kJ mol −1 with ZPE included.…”
Section: Density Functional Theory and Mp2 Studies Of No + H 2 O Andmentioning
confidence: 81%
“…Based on experimental studies, it is believed that nitrous acid, i.e. HONO, formation can occur for n = 4 and becomes dominant for n = 5 [15,16]. DePetris et al [17] studied the minimum energy structures of H 2 NO + 2 and identified six stable minimum energy conformations with Møller-Plesset perturbation theory calculations and concluded that the lowest energy NO + .…”
Section: Introductionmentioning
confidence: 99%
“…Both experimental and theoretical studies confirm that while certain water configurations promote the formation of HONO in the (NO + )Á(H 2 O) 4 cluster, the reaction does not proceed in (NO + )Á(H 2 O) n clusters for n r 3. [24][25][26] This previous work on HONO formation in absence of the NO 3 À anion motivated the choice of water cluster size and configuration in the present study. In previous work by Miller and Gerber, a similar cluster model was employed in studies of N 2 O 4 autoionization as well as proton recombination with the NO 3 À anion.…”
mentioning
confidence: 99%
“…In previous work [37], we observed that the mixed cluster ions, [(NO)(NH 3 ) n ] + , can be considered as having a structure where the ion core NO + is solvated by the ammonia molecules. This picture of NO + solvated by NH 3 is different from that for the mixed cluster ion [(NO)(H 2 O) n ] + [38,39] where the structure of [NO(H 2 O) n ] + cluster ion depends on the cluster sizes n; for n ≤ 3, the ion core is NO solvated by water molecules, while, for n ≥ 4, the [NO(H 2 O) n ] + the cluster ion now exists in the form (H 2 O) n−1 H + ·HONO. Ab initio calculations [40] have also borne out structural changes with an increased number of water molecules within the cluster ions.…”
Section: Methodsmentioning
confidence: 78%